Peningkatan Kemampuan Kader Kesehatan Dalam Deteksi Stunting Pada Balita Menggunakan Media Leaflet di Posyandu Seruni Desa Mapane Tambu - Fitriani Fitriani; Zamli Zamli (Jurnal Pengabdian Masyarakat JUPEMANDO, 2025)
This community service activity aims to increase the knowledge and attitude of Posyandu cadres in early detection of stunting in toddlers. The activity was held at Posyandu Seruni, Mapane Tambu Village, Balaesang District, Donggala Regency, Central Sulawesi, on July 22 - 28, 2025. The main target is 15 active cadres, with mothers under five as indirect beneficiaries. The implementation method includes interactive training, counseling, field practice, and mentoring. The material provided includes the basic concept  of stunting, anthropometric measurement techniques, classification of nutritional status, and health communication using leaflet media. The evaluation was carried out through observation of cadre practice, group discussions, short questionnaires, and oral feedback from participants. The results of the activity showed an increase in cadres' understanding of the concept of stunting and skills in conducting early detection independently. Media leaflets have been proven to help in the educational process for mothers under five. This activity has a positive impact on the readiness of cadres as the spearhead of monitoring child growth and development at the posyandu level. It is hoped that similar training can be carried out on an ongoing basis to strengthen stunting prevention in the community.